Hubungan Antara Persepsi Terhadap Keadilan Kompensasi dengan Komitmen Organisasi di Hospitality Industry - Oktarini, Kadek Ratih Dwi; Indrawati, Komang Rahayu (Jurnal Psikologi Udayana; Vol 1 No 2 (2014), 2014)
The increase number of turnover each year in hospitality industry causes by inappropriate commission. The employee’s perception of inappropriate compensation’s issue will decrease a commitment of employee to the organization that will affect to the discharge of organization. This study aiming to see the relationship between perception of compensation’s justice with organizational commitment in hospitality industry. Methodology this study is a quantitative research that used linier regression technique and two stage cluster sampling technique to collect the sampels. The respondents are an employee at 6 hotels, 3 motels, 1 resort, 3 bars, 2 restaurants, 2 hospitals, and 4 travel agents with 189 employees. Acting as the measuring device in this research is 26 valid items on scale of perception of compensation’s justice ranging between 0,385 to 0,743 and the coefficient reliability is 0,945. While in scale of organizational commitment there were 37 valid items with validity items ranging from 0,247 to 0,688 and the coefficient reliability is 0,939. The statistic analysis result showed that there a positive relationship and significant between perception of compensation’s justice with organizational commitment (r = 0,826, p = 0,000). The aspects perception of compensation’s justice were employee’s is a thought, feelings, and behavior about the justice in giving the compensation. The effective contribution to perception of compensation’s justice with organizational commitment is 68, 2 percent. Futher analysis showed that was a very strongly relationship between perception of compensation’s justice with affective commitment component (r=0,802). Keywords : Perception of compensation’s justice, organizational commitment, and  hospitality indust